Optimalisasi Kinerja Karyawan melalui Penguatan Lingkungan Kerja: Studi Kasus pada Bengkel Mobil Perdana Body Repair di Kota Malang - Sri Hariyanti; Imam Mukhlis (Indonesian Journal of Humanities and Social Sciences, 2023)
Every organization should pay serious attention to the creation of a comfortable and safe working environment for its employees. The quality of the work environment can have a significant impact on employee productivity and performance in carrying out their duties. This study aims to explore the role of the work environment in improving employee performance at the Perdana Body Repair Workshop in Malang City. The research method used is descriptive qualitative using data collection techniques through observation, interviews, and recording or documentation. The results showed that the physical work environment at Perdana Body Repair Workshop in Malang City is considered quite good. Aspects such as cleanliness, lighting, security, equipment, and facility layout reach adequate standards. In addition, the relationship between leaders and employees in the non-physical environment is considered good. The quality of work of employees at Perdana Body Repair Car Workshop Malang City shows a good level, which is reflected in performance indicators such as quality, quantity, and timeliness, cost efficiency, supervision, and relationships between employees. These findings confirm that the work environment has a significant role in improving employee performance at the Perdana Body Repair Workshop in Malang City.